Oracle DBA pocket guide - Kreines, David C. (O'Reilly, 2005)
The Oracle database is one of the most popular in the world, and for good reason. It's compatible, scalable, portable, and capable of performing incredibly fast. The advantages Oracle holds over its competition come with a price, however--it's a highly complex database that's becoming more complex with every release. And this level of detail, of course, can begin to weigh on database administrators (DBAs). Fortunately, the Oracle DBA Pocket Guide from O'Reilly is on the case. This handy reference is designed to help administrators make more effective use of their time by presenting a compact.